The Role Of Product Quality On The Purchase Decisions - Piartrini, Putu Saroyeni (Yayasan Pendidikan Belajar Berdikari, 2024)
The shift in views that happens in individuals who are becoming more oriented toward something quick is a chance to compete with entrepreneurs. This adjustment resulted in the immediate and beautiful presentation of a broad variety of commercial items. The drinking water business sector is now one of the most popular business sectors for micro and medium-sized enterprises, owing to the increasing demand for clean water and the decrease in the availability of clean water, so that packaging water is a solution that allows One of the companies named Balian Water to be the subject of this research. This study is quantitative in its technique, kind, and character. A frequency distribution table, line graph, bar graph, circle diagram, and histogram are common ways to depict data. Quality, pricing, and advertising all have a significant impact on purchasing decisions. Because the quality, pricing, and promotional efforts of a product influence people's purchasing decisions.